Studi Manajemen Makanan di Rumah Sakit X - Puput Mulyono; Singgih Purnomo (Universitas 45 Surabaya, 2023)
One definition of food service management is an integrated system of interconnected activities. Determining the description of Hospital X's food management services is the goal of this study. A qualitative approach is the research design that was employed. The study was conducted at Hospital X. The interview method was employed by the data provider. Purposive sampling was the method of sampling that was employed. The study of hospital food management serves as the univariate variable in this investigation. Triangulation techniques and a qualitative approach are used to explain the research's findings. According to the study's findings, the majority of Hospital X's food services meet standards. In this situation, give the food's color, taste, and portion greater consideration when distributing it.